ALKOLİK YAPILAN GEBE SIÇANLAR VE YAVRULARINDA NK AKTİVASYONU İLE IL-2, IFN-γ ve CD19 ETKİLEŞİMİ - AKYOL, Sibel; TUNALI, Halil; KIRAN, Bayram; İLTER, Özdemir (Cerrahpaşa Medical Journal, 2019)
Background.- Our study aims to show how the NK cells interact with the parameters of IL-2, IFN-y and CD 19 in the alcoholic pregnant rats and their offspring. Several experimental animal models have been described for the study that was carried out on a total number of 80 Wistar albino female rats. Design.- In our study, rats were divided into 8 groups; 1) Control group (K) (n=10) 2) Group that received ethanol through gavage (G) (n=10) 3) Control pregnant group (KG) (n=10) 4) Pregnant group that received ethanol through gavage (GG) (n=10) 5) Control offspring (10 days old) (KY10) (n=10) 6) Control offspring (30 days old) (KY30) (n=10) 7) 10 day-old offspring of pregnant rats that received ethanol through gavage (GY10) (n=10) 8) 30 day old offspring of pregnant rats that received ethanol through gavage (GY30) (n=10). Results.- Data from this study show that there has been a considerable decrease in the NK values the successive groups [(K: % 54.90±10.86 and G: % 38.40±3.43), (KG: % 40.00±2.1 and GG: % 37.1±2.10)] and the groups of 10 to 30 day old offspring of rats [(KY10: %30.2±2.1 and GY10: %13.0±0.7), (KY30: %32.28±2.6 and GY30: %20.75± 1.2)] respectively. A significant decrease is observed in the IL-2 values between the consecutive groups [(K: 86.5±1.3 pg/ml and G: 71.0±2.4 pg/ml), (KG: 65.9±1.1 pg/ml and GG: 60.9±2.1 pg/ml )] and the groups of 10 to 30 day old offspring of rats [(KY10: 75.4±3.2 pg/ml and GY10: 63.0±3.2 pg/ml), (KY30: 76.0±3.4 pg/ml and GY30: 70.0±2.6 pg/ml)] respectively. The IFN-y values indicated a considerable decrease among the successive groups [(K: 1250±29.6 pg/ml and G: 860±27.3 pg/ml) (KG: 720±13.6 pg/ml and GG: 570±9.1 pg/ ml)] and the groups of 10 to 30 day old offspring of rats [(KY10: 850±25.0 pg/ml and GY10: 520±17 pg/ml) (KY30: 900±10 pg/ml and GY30: 640±16.10 pg/ml) ] respectively. No significant changes were observed in the CD-19 values between the groups [(K: % 25.73±3.07 and G: % 23.83±1.6) while there was a significant decrease between the groups (KG: %23.98±1.7 and GG: % 18,46± 1.7)] The CD-19 values displayed a considerable increase among the consecutive groups of [(KY10: %11.15±1.7 and GY10: % 32.5±2.0) (KY30: %21.35±1.2 and GY30: % 30.8±1.8)] respectively. Conclusions.- It has been observed that in the female pregnant rats that received alcohol through gavage, the NK activity falls considerably according to the control group and in parallel to that there is a decrease in the levels of the parameters CD 19, IL-2 and IFN-y. Compared to the 30-day old-offspring, a more suppressive effect was observed in the NK, IL-2 and IFN-ã levels of the 10 day old offspring of the rats that received alcohol during the period of pregnancy. Also in the CD-19 level, a significant increase is observed both in 10 and 30 day old offspring. These results point out the fact that the teratogenic factors like alcohol are primarily responsible for the profound and harmful effects on the special immune tolerance systems that have developed through the period of pregnancy of the mother.